Education governance and privatization in Portugal: Media coverage on public and private education - Fátima Antunes; Sofia Viseu (Arizona State University, 2019)
This paper aims to discuss recent changes in Portugal's education policy. Portugal offers an interesting scenario to study the different ways the economic crisis has brought new opportunities to strengthen the privatization agenda. We specifically focus on media coverage and the contractualization of education services with private schools through 'association contracts'. In the 1980s the Portuguese State through these contracts financed private schools to operate in areas where the public offering was insufficient, thereby ensuring the public access to education and preventing marginalization. Nowadays, however, these contracts are seen as an ideological banner both for and against education privatization. We present an empirical study based on documental analysis of 180 news articles published in the Portuguese media on the changes in the contractualization of education services. The results show two main audiences sustaining distinct societal projects, comprised of a variety of actors, who are either for or against 'association contracts'. The actors justify their positions based on their understanding of the State's role in providing education, the policies involving the right to education and decreasing inequalities.